The Impact of Mudharabah Financing On The Advancement of Beef Cattle Industry - Cahyani, Adisti; Khoiriyah, Rahmawati (Jurnal Iqtisaduna, 2023)
The study aims to determine the role of mudharabah financing on the development of beef cattle business in Boyolali. Mudharabah financing is a partnership contract based on the principle of profit sharing by means of one person providing his capital to another to conduct business and both parties share the profits or bear the burden of losses based on the contents of a joint agreement. MSMEs are used as an alternative to creating new jobs or jobs for the community, MSMEs have a very large function and role in encouraging the pace of economic growth. In this study using quantitative methods with primary data or questionnaire distribution as a source of data to be tested in this study and the object of research is beef cattle business. The respondents based on this study are Boyolali people who have a beef cattle business of 40 people / sample. This study used a simple linear regression test and a T test. the conclusion of the data processing results showed that the test results were partially obtained by the T Test, the significance value of 0.000 < 0.05, which means that there is a significant influence between mudharabah financing (X1) on the development of MSMEs (Y). And the regression coefficient of mudharabah financing of 0.619 means that the variable mudharabah financing (X) has a positive effect on the development of MSMEs (Y).